PURPOSE AND CHARACTERISTICS OF SPORTS ACTIVITIES: PURPOSE AND CHARACTERISTICS OF SPORTS ACTIVITIES - Koldashev, Sirojjon (Физическое воспитание, спорт и здоровье, 2022)
In this article, sports improvement in the training process involves the use of the entire complex of training and extracurricular factors, which allows you to purposefully influence the development of an athlete and, ultimately, increase his physical level